2010
DOI: 10.1172/jci42106
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 4 regulates osteoclast differentiation in mice

Abstract: Activating transcription factor 4 (ATF4) is a critical transcription factor for osteoblast (OBL) function and bone formation; however, a direct role in osteoclasts (OCLs) has not been established. Here, we targeted expression of ATF4 to the OCL lineage using the Trap promoter or through deletion of Atf4 in mice. OCL differentiation was drastically decreased in Atf4 -/-bone marrow monocyte (BMM) cultures and bones. Coculture of Atf4 -/-BMMs with WT OBLs or a high concentration of RANKL failed to restore the OCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 68 publications
5
99
0
Order By: Relevance
“…Elevated levels of ISR markers (such as ATF4 or eIF2α phosophorylation) in the liver of NFR-treated mice suggest that activation of this pathway may contribute to the side effects observed in HIV-PI-treated patients. Indeed, ATF4 is known to play a key role in osteoblast differentiation (53) and its transgenic expression in osteoclasts promotes severe osteopenia (54). Therefore, bone diseases found in HIV-PI-treated patients could be linked to the deregulation of this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of ISR markers (such as ATF4 or eIF2α phosophorylation) in the liver of NFR-treated mice suggest that activation of this pathway may contribute to the side effects observed in HIV-PI-treated patients. Indeed, ATF4 is known to play a key role in osteoblast differentiation (53) and its transgenic expression in osteoclasts promotes severe osteopenia (54). Therefore, bone diseases found in HIV-PI-treated patients could be linked to the deregulation of this transcription factor.…”
Section: Discussionmentioning
confidence: 99%
“…ATF4 binds to the promoter and activates expression of the receptor activator of NF-κB ligand (RANKL; Tnfsf11). RANKL is a factor secreted by osteoblasts that binds to its receptor (RANK) on osteoclasts to trigger intricate and distinct signaling cascades that control osteoclast lineage commitment and activation (Cao et al 2010). Thereby, ATF4 promotes bone formation.…”
Section: Atf4mentioning
confidence: 99%
“…Its protein binds DNA via their basic regions and dimerize via their leucine zipper domain to form a variety of homo-and heterodimers to regulate gene transcription (De Angelis et al 2003). It was demonstrated that Atf4 plays a direct role in regulating osteoclast (OCLs) differentiation and findings suggest that it may be a therapeutic target for treating bone diseases associated with increased OCL activity (Cao et al 2010). It is also known that Aft4 influenced the diet-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that an atherogenic diet inhibits bone formation by blocking differentiation of osteoblasts in growing mice, possibly resulting from lipid oxidation products (Parhami et al 2001). A recent study has suggested that a HFD may induce an increase in bone resorption in mice (Cao et al 2009(Cao et al , 2010. However, HFD can also have positive effects as shown in the diabetes-prone BioBreeding/OttawaKarlsburg (BB/OK) rat that is an excellent animal model for type 1 diabetes (Yang and Santamaria 2006;Bahr et al 2011).…”
Section: Introductionmentioning
confidence: 99%